2022
DOI: 10.2174/1573412918666220118113546
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Carbohydrate-based Polyurethane: From Biosynthesis to Degradation

Abstract: The foremost common natural polymers are carbohydrate-based polymers or polysaccharides, having a long chain of monosaccharide or disaccharide units linked together via a glycosidic linkage to form a complex structure. There are several uses of carbohydrate-based polymers in biomedical sector due to its attractive features including less toxicity, biocompatibility, biodegradability, high reactivity, availability, and relatively inexpensive. The aim of our study was to explore the synthetic approaches for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
0
1
0
Order By: Relevance
“…Progress in the field of polyurethanes led to several innovative biomedical areas ranging from drug delivery to tissue engineering [120]. Consequently, polyurethanes have been frequently used to form drug delivery carriers, stents, catheters, adhesives, coatings, bioimplants, and other tissue engineering scaffolds [121][122][123]. Accordingly, polyurethane foam materials have been developed and applied for numerous in vivo and in vitro uses [124,125].…”
Section: Biomedical Field Applicationsmentioning
confidence: 99%
“…Progress in the field of polyurethanes led to several innovative biomedical areas ranging from drug delivery to tissue engineering [120]. Consequently, polyurethanes have been frequently used to form drug delivery carriers, stents, catheters, adhesives, coatings, bioimplants, and other tissue engineering scaffolds [121][122][123]. Accordingly, polyurethane foam materials have been developed and applied for numerous in vivo and in vitro uses [124,125].…”
Section: Biomedical Field Applicationsmentioning
confidence: 99%
“…The results of recent studies indicated that sodium nanoalginate is a cheap and environmentally friendly material [32,33]. Sodium nanoalginate also holds good thermal and mechanical stability and has a high self-healing capability when exposed to air [34,35]; it is soluble in hot and cold water, obtained by dissolving a liquid with high viscosity, and forms irreversible gels in reaction with calcium salts or acids. Sodium nanoalginate gels hold characteristics such as viscosity and material stabilization properties [36,37].…”
Section: Introductionmentioning
confidence: 99%